Is mifepristone better than dinoprostone gel for induction of labor at term? Feto-maternal outcome in tertiary referral hospital - Krishna, K. Sowmya; Vellanki, Janaki (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: The global increase in labor inductions has resulted in corresponding rise in failed inductions, instrumental deliveries and c-section rates significantly contributing to feto-maternal morbidity and mortality indicating critical need for better induction methods ensuring safer outcomes with minimal complications. This study compares 200mg oral mifepristone with 0.5mg intracervical dinoprostone gel for labor induction in latent phase at term gestation, focusing on safety, efficiency, complications and feto-maternal outcomes. Methods: This was a prospective, randomized comparative study conducted at Gandhi Hospital, a tertiary healthcare teaching institute, from April to June 2024 admitted for safe confinement after 37 completed weeks of gestation in OBG department, divided into Group A and B (75 each) receiving 200mg oral mifepristone and 0.5mg intracervical dinoprostone gel respectively. Results: The induction delivery interval was significantly shorter in Group B compared to Group A. However, the rate of successful induction of labor (IOL) or vaginal delivery was higher in Group A. Group B had higher rate of interventional deliveries including vacuum, forceps delivery or LSCS, with more maternal complications & NICU admissions. Conclusions: It concludes that mifepristone is a better drug reducing the need for additional prostaglandins or other induction methods and has modest effect on cervical ripening for labor induction at term with lesser complications despite longer induction delivery interval compared to dinoprostone. Therefore, mifepristone is a safe, efficient and cost-effective drug offering easy patient compliance and application.